Nephroprotective efficacy of Asparagus racemosus root extract on acetaminophen-induced renal injury in rats - Roy, Suchismita; Pradhan, Shrabani; Mandal, Shreya; Das, Koushik; Nandi, Dilip Kumar (Acta Biologica Szegediensis, 2018)
Acetaminophen-induced renal necrosis and insufficiency occurs in patients with acetaminophen overdose. Renal failure is rapidly assuming epidemic proportions globally. In absence of reliable and effective nephroprotective drugs, strategies towards exploring alternative therapies for treatment of kidney diseases are essential. Asparagus racemosus is a medicinal plant used for treatment of various ailments. This research was undertaken to investigate the protective effect of ethanol fraction of A. racemosus roots extract in acetaminophen-induced uraemia and renal failure in rats. Rats were co-administered with acetaminophen injection and oral administration of A. racemosus roots extract in an attempt of protection against renal failure. Uremic biomarkers significantly decreased, and elevated levels of antioxidant enzymes were found, in the animals treated with ethanol fraction of A. racemosus when compared with acetaminophen treated uremic animals. Also, histology of kidneys showed control like structure in animals treated with this extract but severe damage in the uremic animals. HPLC analysis of the ethanol fraction of A. racemosus roots extract revealed eight compounds out of which one had a retention time near to the quercetin standard. It may be concluded that this extract of A. racemosus has therapeutically useful nephroprotective potential.